CURCUMİN'İN STRES ÜLSERLERE ETKİSİ - USLU, Ezel (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Curcumin is a phenolic compound known with its antioxidant properties. In this study we have evaluated if curcumin has antiulcerogenic properties as well. For the study twenty wistar rats were evaluated. Brodie.s immobility method was performed for inducing stress ulcers. Sialic acid, a component of mucus glycoproteins, protects gastric mucosa against ulcerogenic stress, via conferring resistance against proteolytic cleavage. Sialic acid determination was performed according to thiobarbituric acid assay of Warren. Results.- We have evaluated sialic acid levels in gastric mucosa and plasma of rats. In the rats fed with curcumin dissolved in sesame oil, neither plasma nor mucosal sialic acid levels did not significantly differ from rats, which only fed sesame oil (p>0.05). Conclusions.- Any protective effect against stress ulcers was not found for curcumin and hence an antioxidant property alone could not significantly modulate this process.